MEASURING THE EFFECT OF SOCIAL NETWORKING, ORGANIZATIONAL CULTURE TOWARD EMPLOYEE ENGAGEMENT IN SOES ORGANIZATION: CASE STUDY OF SOES IN INDONESI - wiley, victor; Lucas, Thomas (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.02.TAHUN 2020, 2020)
SOEs in Indonesia has been expanded their project with tight time and more challenged business climate. In fact, similar to private organization, SOEs also faced with employee performance in their projects. The employee performance has many aspects of social networking, organizational culture and employee engagement. This study tested the influence of social networking, organizational culture and employee engagement on in several projects which ventured by State Owned Enterprises in Indonesia. The variables are analyzed by using SEM AMOS. It is explained that social networking, organizational culture and employee engagement affect employee engagement in SOEs-based projects in Indonesia. This study suggested an approach to improve social networking, organizational culture and employee engagement as new strategies for SOEs in Indonesia. This study result can be a recommendation to the SOEs managers to maintain social networking, organizational culture and employee engagement in order their project to be manageable.